The Association between Perceived Social Support, Perceived Stress, Coping Strategies and Quality of Life in Pregnant Females - Ahmad, Ayesha; Mushtaq, Rabia (Annals of Human and Social Sciences, 2024)
This study investigated the predictive association of perceived social support, perceived stress, coping with the quality of life of pregnant women in Pakistan. Motherhood is transformative journey of fulfillment, and involves physiological and emotional shifts, impacting QoL. Social support and effective coping helps mother to reduce the detrimental effects of stress and maintain QoL. 200 pregnant females were selected from the Gynecology departments of various hospitals of Karachi, Pakistan by using purposive sampling technique. Semi-structured interview form, Urdu versions of Multidimensional Scale of Perceived Social Support, Perceived Stress Scale, Coping Strategy Questionnaire-Short Form, and Quality of Life Questionnaire for Physiological Pregnancy were administered. Perceived social support, perceived stress and coping strategies have been found as significant predictors of QOL. The development and implementation of health friendly policies and interventions for pregnant ladies can play a significant role throughout pregnancy, and after child birth to maintain the QoL of both the mother and child.